An electrospun PI@PMIA nanofiber diaphragm for zinc ion battery and preparation method thereof

Pi@PMIA nano -fiber membrane is prepared through electrostatic spinning technology to solve the problem of poor mechanical properties and short service life of zinc ion battery diaphragm, and achieve higher thermal stability, mechanical performance and service life to prevent zinc branches from piercing penetration And extend the battery life.

CN115275506BActive Publication Date: 2025-01-28TIANJIN POLYTECHNIC UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210780649.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-05
Publication Date
2025-01-28
Estimated Expiration
2042-07-05

AI Technical Summary

Technical Problem

The existing zinc-ion battery separators have problems with poor mechanical properties and short service life in zinc dendrites puncture, resulting in short circuits in the battery.

Method used

Use static spinning technology to prepare PI@PMIA nano -fiber film, provide heat stability and mechanical properties through PI fiber, PMIA fiber promote electrolyte affinity and gel degree, thereby forming a multi -functional gel with both softness and strength Battery diaphragm.

Benefits of technology

Improve the thermal stability, mechanical performance and service life of zinc ion battery septum, prevent zinc branch crystals from piercing, extend the working life of the battery, and improve the stability and reversibility of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115275506B_ABST
    Figure CN115275506B_ABST
Patent Text Reader

Abstract

The present invention provides a polyimide@polyisophthalamide (PI@PMIA) nanofiber diaphragm for zinc ion batteries and a preparation method thereof, and belongs to the technical field of diaphragm preparation. It is characterized in that: PI nanofibers and PMIA nanofibers are interwoven and distributed, the fibers are long-range continuous, and the diameters are distributed between 50-500nm. At the same time, the PI@PMIA zinc ion battery diaphragm has excellent porosity, uniform pore size, good hydrophilicity and excellent breaking strength. The preparation method comprises the following four steps: (1) configuration of PAA spinning solution; (2) configuration of PMIA spinning solution; (3) synchronous multi-needle electrospinning; and (4) calcination treatment. The PI@PMIA battery diaphragm prepared by the present invention coordinates the excellent performance of PI and PMIA components, is a multifunctional fiber diaphragm with both softness and strength, and the preparation method is simple and easy, which provides a new idea for the development of a novel nanofiber diaphragm for zinc ion batteries with excellent electrochemical performance and long cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of zinc ion batteries, and in particular to an electrospun PI@PMIA nanofiber diaphragm for zinc ion batteries and a preparation method thereof. Background Art

[0002] In recent years, there is an urgent need to develop efficient and sustainable energy storage technologies. Batteries are the most common energy storage devices in people's lives today, and the commercial lithium-ion battery preparation technology has already occupied an important position in electronic energy storage. However, the active chemical properties of metallic lithium and the high cost of organic electrolytes have restricted the widespread application of lithium-ion batteries in large-scale energy storage and smart wearable fields.

[0003] Aqueous zinc-ion batteries have excellent mass capacity (820 mAh g -1 ) and volumetric capacity (5854 mAhcm -3 ), a wide electrochemical operation window, and a low redox potential (-0.76V vs standard potential). More importantly, zinc-ion batteries are safe, low-cost, easy to process, environmentally friendly, and have high ionic conductivity. These advantages make zinc-ion batteries have broad prospects for application in large-scale energy storage and smart wearables. However, the zinc anode is prone to form rough and irregular dendrites during charging. Once zinc dendrites with ultra-high Young's modulus (108GPa) are formed, they will penetrate the diaphragm and cause a short circuit, thus hindering the excellent performance and practical industrialization of zinc-ion batteries. The growth of zinc dendrites includes the following two aspects: on the one hand, the zinc anode surface with uneven electric field distribution preferentially deposits zinc ions during the electroplating / stripping process, which promotes the growth of zinc dendrites and the tip effect; on the other hand, water-induced side reactions (such as hydrogen evolution and corrosion) will cause more defects on the zinc anode surface, thereby accelerating the growth of dendrites.

[0004] So far, a lot of research has been done to inhibit dendrite formation and protect the zinc anode, and most of the current research focuses on the design of zinc anode and electrolyte, such as providing physical protection by introducing coatings or adjusting the electrolyte-electrode interface; constructing a three-dimensional structure to increase the surface area of ​​the zinc anode, controlling the zinc nucleation site for electrode modification; adding electrolyte additives or developing new electrolyte salts to coordinate ion transport, homogenize the interfacial electric field, and induce zinc deposition, etc. However, there are relatively few studies on the use of new battery separators to stabilize zinc-ion batteries.

[0005] As we all know, the separator, as a component of the battery, not only allows ion transport but also avoids direct contact between the positive and negative electrodes, which means it plays a vital role in improving the safety characteristics and electrochemical performance of the battery. Currently, zinc-ion batteries mainly use glass fiber (GF) separators with a thickness of several hundred microns due to its good compatibility with aqueous electrolytes and high ionic conductivity. Unfortunately, its poor mechanical properties and large pore size make it easily pierced by dendrites, resulting in battery short circuit. Considering these shortcomings, researchers have made many efforts to overcome the shortcomings of GF separators, usually by adding foreign species or constructing additional protective layers (1. C. Li, ZT Sun, T. Yang, et al, Adv. Mater., 2020, 32, 2003425. 2. J. Cao, DD Zhang, XY Zhang, et al, J. Mater. Chem. A, 2020, 8, 9331-9344.), which is likely to increase the cost of the separator and even destroy the energy density of the entire device due to the inevitable increase in weight and volume. The nanofiber membrane prepared by electrospinning technology has the characteristics of large liquid absorption rate and fine diameter, high specific surface area, high porosity and excellent ionic conductivity, and is a popular research direction of ion battery separators in recent years. It is worth noting that research in the field of electrospinning to prepare lithium metal battery separators has been reported, such as patent CN112768834A preparing lithium sulfur battery separators by electrospinning polyacrylonitrile / sulfonated polyetheretherketone; patent CN110565269A using coaxial electrospinning to prepare lithium battery separators. However, there is still a lot of work to be done on the research of zinc ion battery separators. Summary of the invention

[0006] The purpose of the present invention is to provide an electrospun PI@PMIA zinc ion battery separator and a preparation method thereof, so as to improve the problems of poor mechanical properties, short service life and uneven ion transmission of existing separators. The present invention adopts an electrospinning process to prepare a PI@PMIA nanofiber membrane with high porosity, large specific surface area and coarse and fine structure. Among them, the coarser PI fibers provide excellent thermal stability and mechanical properties, and can maintain a relatively high wet fracture strength even after soaking, and can provide a strong skeleton support for the separator to resist the growth of zinc dendrites, thereby preventing the dendrites from piercing the separator and causing battery short circuit. The finer PMIA fibers have good thermal stability, excellent electrolyte affinity and significant gelation degree, which is conducive to the formation of gel electrolyte. More importantly, the gel part can prevent the leakage of liquid electrolyte and provide a closer contact interface with the electrode to promote ion transport and interface stability. The PI@PMIA nanofiber membrane prepared by the present invention can cooperate with the excellent performance of PI and PMIA components to become a multifunctional gel battery separator with both softness and strength.

[0007] To achieve the above object, the present invention provides the following solutions:

[0008] The present invention provides a method for preparing an electrospun PAA@PMIA nanofiber membrane, comprising the following steps: (1) preparing a PAA spinning solution; (2) preparing a PMIA spinning solution; and (3) preparing a PAA@PMIA nanofiber membrane with a coarse and fine structure by synchronous multi-needle electrospinning.

[0009] Furthermore, the preparation of the PAA spinning solution includes the following steps: PAA is synthesized by ODA monomer and PMDA monomer, a certain mass of solvent DMF is weighed into a beaker, and then the ODA monomer is added, and after the ODA is completely dissolved, the PMDA monomer is slowly added and continuously stirred for 4-6 hours, and finally a transparent light yellow PAA spinning solution is obtained; the concentration of the PAA spinning solution is 18-28%, and the molar ratio of the ODA and PMDA monomers is 1:1; the spinning voltage is 25-30 kV, the distance between the spinning needle and the receiving device is 17-20 cm, and the PAA spinning solution is driven by a micro-injection pump, and the extrusion rate is controlled at 0.7-1.0 mL h -1 .

[0010] Furthermore, the preparation of PMIA spinning solution includes the following steps: first weighing a certain mass of solvent DMAc into a beaker, then adding PMIA resin and stirring continuously for 2-3 hours to obtain a uniform and transparent PMIA spinning solution; the PMIA spinning solution concentration is 25-35%, the spinning voltage is 30-35 kV, the distance between the spinning needle and the receiving device is 16-18 cm, and the PMIA spinning solution is driven by a micro-injection pump, and the extrusion rate is controlled at 0.6-0.8 mL h -1 .

[0011] Furthermore, the preparation of electrospun PAA@PMIA nanofiber membrane includes the following steps: (1) adding the evenly stirred PMIA and PAA spinning solutions to two pipettes placed in the same horizontal direction, respectively, and selecting a flat needle with a diameter of 0.8 mm as the electrospinning needle; (2) connecting the spinning needle to the conductive clip of the high-voltage power supply, the receiving device used is a metal drum, and the receiving device is grounded by a wire; (3) turning on the electrospinning machine and the high-voltage power supply, so that PMIA and PAA nanofibers are continuously deposited along the metal drum, and after a period of time, a layer of nanofiber film can be formed on the metal drum.

[0012] The present invention also provides an electrospun PI@PMIA zinc ion battery separator, which is prepared by calcining the PAA component of the PAA@PMIA nanofiber membrane to achieve imidization.

[0013] Furthermore, the calcination method includes at least one of hot press heating, muffle furnace heating, and oven heating.

[0014] Furthermore, the heating rate of the PAA@PMIA nanofiber membrane was controlled at 2-5°C / min, and after heating to 280°C-300°C, the constant temperature was maintained for 1-3h to obtain the PI@PMIA nanofiber battery separator.

[0015] The present invention discloses the following technical effects:

[0016] In the PI@PMIA composite zinc ion battery separator prepared by the present invention, PI with excellent thermal stability and mechanical properties and PMIA with good thermal stability, excellent electrolyte affinity and significant gelation degree are prepared by one-step electrospinning. The PI@PMIA nanofiber battery separator prepared by the present invention can coordinate the excellent performance of PI and PMIA components, effectively regulate the transfer of zinc ions in the separator and promote the uniform deposition of zinc ions on the surface of the zinc negative electrode, thereby ensuring the high stability and reversibility of the zinc ion battery.

[0017] The PI@PMIA composite zinc ion battery separator prepared by the preparation method of the present invention has good hydrophilicity, high porosity, excellent mechanical properties, high chemical stability, long service life, environmental friendliness, and high ion conduction efficiency, and can be used as a multifunctional gel battery separator with both softness and strength. The preparation method of the present invention is simple, easy to operate, effective, environmentally friendly, and suitable for large-scale low-cost production. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0019] Figure 1 This is a scanning electron micrograph of the PI@PMIA composite zinc ion battery separator prepared in Example 1;

[0020] Figure 2 This is a scanning electron micrograph of the PI@PMIA composite zinc ion battery separator prepared in Example 2;

[0021] Figure 3 This is a scanning electron micrograph of the PI@PMIA composite zinc ion battery separator prepared in Example 3;

[0022] Figure 4 This is a scanning electron microscope image of the PI@PMIA composite zinc ion battery separator prepared in Example 4;

[0023] Figure 5 The impedance diagram of the Zn / GF / MnO2 and Zn / PI@PMIA / MnO2 full cells in Example 5;

[0024] Figure 6 The Zn / GF / Zn and Zn / PI@PMIA / Zn cells in Example 6 were tested at 1 mA cm -2 Constant current charge and discharge test diagram under current density and its polarization voltage (inset);

[0025] Figure 7 The Zn / GF / MnO2 and Zn / PI@PMIA / MnO2 batteries in Example 7 at different current densities (0.1-2A g -1 ) magnification diagram. DETAILED DESCRIPTION

[0026] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0027] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0028] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0029] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0030] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0031] In the present invention, all raw materials are conventional commercially available raw materials.

[0032] In the present invention, the specific operation of preparing PI@PMIA nanofiber membrane includes four steps: (1) preparation of PAA spinning solution; (2) preparation of PMIA spinning solution; (3) synchronous multi-needle electrospinning process; (4) calcination treatment, converting PAA nanofibers into PI nanofibers through imidization, and finally obtaining PI@PMIA nanofiber membrane, and adjusting the membrane thickness by adjusting the spinning time.

[0033] Example 1

[0034] (1) Preparation of PAA spinning solution: First, weigh 2.68 g of ODA monomer and fully dissolve it in 14.4 g of DMF solvent. After ODA is completely dissolved, slowly add 2.92 g of PMDA. After mechanical or magnetic stirring at 25-35° C. for 5-7 h, a transparent light yellow PAA spinning solution with a mass fraction of 28% is obtained.

[0035] (2) Preparation of PMIA spinning solution: To prepare PMIA spinning solution, 10 g of PMIA resin with a mass fraction of 25% was uniformly added into 7.2 g of DMAc, and then mechanically or magnetically stirred at 45° C. for 2-3 h to obtain a uniform and transparent PMIA spinning solution with a mass fraction of 25%.

[0036] (3) Synchronous multi-needle electrospinning process: The evenly stirred PMIA and PAA spinning solutions were added into two pipettes placed in the same horizontal direction, and a flat needle with a diameter of 0.8 mm was selected as the electrospinning needle. The spinning needle was connected to the conductive clip of the high-voltage power supply, and the receiving device was a metal drum. The PAA spinning voltage was 30 kV, the distance between the spinning needle and the receiving device was 18 cm, and the flow rate of the PAA spinning solution was controlled at 0.8 mL h -1 The PMIA spinning voltage was 32 kV, the distance between the spinning needle and the receiving device was 18 cm, and the flow rate of the PMIA spinning solution was controlled at 0.7 mL h -1 ; PMIA and PAA nanofibers are continuously deposited along the metal drum, and finally a PAA@PMIA nanofiber film with a thickness of 87 μm is collected.

[0037] (4) Calcination: The PAA nanofibers were heated in a muffle furnace to complete the imidization process and convert into PI. The heating rate during the calcination process was 4°C / min. After the temperature was raised to 300°C, the temperature was kept constant for 2 h to complete the imidization and obtain the PI@PMIA nanofiber membrane.

[0038] Example 2

[0039] (1) Preparation of PAA spinning solution: First, weigh 2.68 g of ODA monomer and fully dissolve it in 14.4 g of DMF solvent. After ODA is completely dissolved, slowly add 2.92 g of PMDA. After mechanical or magnetic stirring at 25-35° C. for 5-7 h, a transparent light yellow PAA spinning solution with a mass fraction of 28% is obtained.

[0040] (2) Preparation of PMIA spinning solution: To prepare PMIA spinning solution, 10 g of PMIA resin with a mass fraction of 25% was uniformly added into 7.2 g of DMAc, and then mechanically or magnetically stirred at 30-45° C. for 2-3 h to obtain a uniform and transparent PMIA spinning solution with a mass fraction of 25%.

[0041] (3) Synchronous multi-needle electrospinning process: The evenly stirred PMIA and PAA spinning solutions were added to two pipettes placed in the same horizontal direction, and a flat needle with a diameter of 0.8 mm was selected as the electrospinning needle. The spinning needle was connected to the conductive clip of the high-voltage power supply, and the receiving device was a metal drum. The PAA spinning voltage was 35 kV, the distance between the spinning needle and the receiving device was 20 cm, and the flow rate of the PAA spinning solution was controlled at 0.7 mL h -1 The PMIA spinning voltage was 32 kV, the distance between the spinning needle and the receiving device was 18 cm, and the flow rate of the PMIA spinning solution was controlled at 0.7 mL h -1 ; PMIA and PAA nanofibers are continuously deposited along the metal drum, and finally a PAA@PMIA nanofiber film with a thickness of 95 μm is collected.

[0042] (4) Calcination: Heat treatment was performed using a hot press to convert the PAA nanofibers into PI after the imidization process. The heating rate during the calcination process was 3°C / min, and the temperature was kept constant at 280°C for 3 h to complete the imidization process, thereby obtaining a PI@PMIA nanofiber membrane.

[0043] Example 3

[0044] (1) Preparation of PAA spinning solution: First, weigh 2.68 g of ODA monomer and fully dissolve it in 14.4 g of DMF solvent. After ODA is completely dissolved, slowly add 2.92 g of PMDA. After mechanical or magnetic stirring at 25-35° C. for 5-7 h, a transparent light yellow PAA spinning solution with a mass fraction of 28% is obtained.

[0045] (2) Preparation of PMIA spinning solution: To prepare PMIA spinning solution, 10 g of PMIA resin with a mass fraction of 25% was uniformly added into 7.2 g of DMAc, and then mechanically or magnetically stirred at 30-45° C. for 2-3 h to obtain a uniform and transparent PMIA spinning solution with a mass fraction of 25%.

[0046] (3) Synchronous multi-needle electrospinning process: The evenly stirred PMIA and PAA spinning solutions were added into two pipettes placed in the same horizontal direction, and a flat needle with a diameter of 0.8 mm was selected as the electrospinning needle. The spinning needle was connected to the conductive clip of the high-voltage power supply, and the receiving device was a metal drum. The PAA spinning voltage was 30 kV, the distance between the spinning needle and the receiving device was 18 cm, and the flow rate of the PAA spinning solution was controlled at 0.8 mL h -1 The PMIA spinning voltage was 35 kV, the distance between the spinning needle and the receiving device was 16 cm, and the flow rate of the PMIA spinning solution was controlled at 0.8 mL h -1 ; PMIA and PAA nanofibers are continuously deposited along the metal drum, and finally a PAA@PMIA nanofiber film with a thickness of 86 μm is collected.

[0047] (4) Calcination: The PAA nanofibers were heated in a muffle furnace to complete the imidization process and convert into PI. The heating rate during the calcination process was 4°C / min. After the temperature was raised to 300°C, the temperature was kept constant for 2 h to complete the imidization and obtain the PI@PMIA nanofiber membrane.

[0048] Example 4

[0049] (1) Preparation of PAA spinning solution: First, weigh 2.68 g of ODA monomer and fully dissolve it in 14.4 g of DMF solvent. After ODA is completely dissolved, slowly add 2.92 g of PMDA. After mechanical or magnetic stirring at 25-35° C. for 5-7 h, a transparent light yellow PAA spinning solution with a mass fraction of 28% is obtained.

[0050] (2) Preparation of PMIA spinning solution: To prepare PMIA spinning solution, 10 g of PMIA resin with a mass fraction of 25% was uniformly added into 7.2 g of DMAc, and then mechanically or magnetically stirred at 30-45° C. for 2-3 h to obtain a uniform and transparent PMIA spinning solution with a mass fraction of 25%.

[0051] (3) Synchronous multi-needle electrospinning process: The evenly stirred PMIA and PAA spinning solutions were added to two pipettes placed in the same horizontal direction, and a flat needle with a diameter of 0.5 mm was selected as the electrospinning needle. The spinning needle was connected to the conductive clip of the high-voltage power supply, and the receiving device was a metal drum. The PAA spinning voltage was 35 kV, the distance between the spinning needle and the receiving device was 20 cm, and the flow rate of the PAA spinning solution was controlled at 0.7 mL h -1 The PMIA spinning voltage was 35 kV, the distance between the spinning needle and the receiving device was 18 cm, and the flow rate of the PMIA spinning solution was controlled at 0.8 mL h -1 ; PMIA and PAA nanofibers are continuously deposited along the metal drum, and finally a PAA@PMIA nanofiber film with a thickness of 93 μm is collected.

[0052] (4) Calcination: The PAA nanofibers were heated in a muffle furnace to complete the imidization process and convert into PI. The heating rate during the calcination process was 5°C / min, and the temperature was kept constant for 2 hours after being heated to 300°C to complete the imidization, thereby obtaining a PI@PMIA nanofiber membrane.

[0053] Example 5

[0054] The prepared PI@PMIA nanofiber battery separator was assembled into a button cell (C2032 type) to test its electrochemical performance. The positive electrode includes a positive electrode current collector (titanium foil) and an active material (MnO2) coated on the positive electrode current collector; the thickness of the positive electrode is 20μm to 500μm. The negative electrode uses commercially available zinc foil; the thickness of the negative electrode is 10μm to 300μm. The electrolyte is an inorganic salt containing anions and cations and having ionic conductivity, preferably at least one of zinc sulfate and zinc trifluoromethanesulfonate, and the solution concentration is 1 to 3 mol / L. Figure 5 The button-type Zn / PI@PMIA / MnO2 full cell was assembled for the PI@PMIA nanofiber battery separator (abbreviated as PI@PMIA), and 2 mol / L zinc sulfate solution was used as the electrolyte. The CHI660D electrochemical workstation was used in the frequency range of 10 -4 ~10 -2 Hz, the electrochemical impedance spectrum tested under the condition of amplitude of 5mV. Among them, the comparative example selected a commercial glass fiber (GF) separator to assemble a Zn / GF / MnO2 full battery.

[0055] Example 6

[0056] The method for preparing PI@PMIA nanofiber battery separator is the same as that in Example 1, and button-type Zn / PI@PMIA / Zn pair batteries are assembled. 2 The polarization voltage is tested under current density, and the test curve is as follows Figure 6 As shown. It can be seen that when the discharge capacity is 1 mAh cm -2 , 1mA cm -2 At a current density of 1.5 Å, the voltage curve of the battery assembled with the GF membrane suddenly dropped after 200 h, indicating the presence of a short circuit. In contrast, the battery assembled with the PI@PMIA membrane can work for more than 700 h, with a longer lifespan, indicating the superiority of the PI@PMIA nanofiber membrane in terms of cycle life. More importantly, the battery assembled with the PI@PMIA nanofiber membrane has a lower voltage hysteresis of 44.8 mV, which is lower than the 64.9 mV of the commercial GF membrane. This is because the PI@PMIA membrane with a uniform pore structure and high porosity can greatly promote the uniform deposition of zinc, resulting in a smaller charge transfer resistance when the battery is working.

[0057] Example 7

[0058] The method for preparing PI@PMIA nanofiber battery separator is the same as that in Example 1. The button-type Zn / PI@PMIA / MnO2 full battery is assembled, and the continuous cycle test at different rates is carried out in the cycle test system to determine its rate performance. 0.1, 0.2, 0.5, 1, 2, 1, 0.2Ag are selected respectively. -1 The current density was 5, and the cycle number was 5 at each rate. The specific capacity retention rate and specific capacity recovery rate of the battery were observed. The test curve is shown in Figure 7 As shown in the figure, the Zn / PI@PMIA / MnO2 full battery can not only work normally at different current densities and has excellent rate performance, but also has a higher battery capacity than the Zn / GF / MnO2 full battery.

[0059] Comparative Example 1

[0060] Same as Example 1, except that the concentration of the PAA spinning solution is 20%.

[0061] Comparative Example 2

[0062] Same as Example 1, except that the concentration of PMIA spinning solution is 32%.

[0063] Comparative Example 3

[0064] Same as Example 1, except that the concentration of the PAA spinning solution is 20%; the concentration of the PMIA spinning solution is 32%.

[0065] Test Example 1

[0066] The performance tests were performed on the PI@PMIA nanofiber battery separators of Examples 1 to 4 and Comparative Examples 1 to 3.

[0067] 1. Porosity determination method: The porosity of different diaphragms is measured by calculation method: a square sample with a size of 2 cm × 2 cm is cut and the thickness of the membrane is measured as h, and the weight is recorded as M0; the density of the diaphragm component is queried as ρ, and the porosity of the diaphragm is calculated by the following formula:

[0068]

[0069] Where: P-porosity (%); M0-sample mass; h-sample thickness; ρ-sample theoretical density.

[0070] 2. Aperture test method: The diaphragm aperture is tested using the Porolux 1000 gas-liquid interface aperture tester from Promet Co., Ltd. of Belgium. The sample to be tested is cut into a disc with a diameter of about 0.6 cm, soaked in the infiltration liquid (Porefil solution) for 10 minutes, and transferred to the fixture with tweezers. The pressure range is set at 0-2 bar.

[0071] 3. Contact angle measurement method: JYSP-180 dynamic contact angle measuring equipment is used to characterize the hydrophilicity of the diaphragm, and the electrolyte contact angle of the diaphragm is measured in combination with the software.

[0072] 4. Mechanical properties test method: The mechanical properties of the diaphragm are tested using a YG005E electronic monofilament fiber reinforcement machine. Test conditions: The cut sample is 40mm×5mm, and the pre-tension is 10cN. The breaking strength and breaking elongation of the sample can be obtained from the test results. According to the strength definition, the following formula is used to calculate the strength of the diaphragm (MPa).

[0073]

[0074] Where: P-film breaking strength (cN), d-film thickness (μm), b-film width (cm).

[0075] The test results of porosity, pore size, contact angle and fracture strength are shown in Table 1.

[0076] Table 1

[0077] project Porosity (%) Pore ​​size (μm) Contact angle (°) Breaking strength(MPa) Example 1 88 28.7 18 4.7 Comparative Example 1 87 28.5 15 4.3 Example 2 91 24.6 12 4.4 Comparative Example 2 90 24.9 14 4.2 Example 3 92 26.5 11 4.2 Comparative Example 3 89 27.5 10 4.5 Example 4 85 27.6 17 4.8 Commercial GF diaphragm 79 40.4 20 0.4

[0078] As shown in Table 1, the PI@PMIA nanofiber battery separator prepared in the present invention has a porosity of up to 88% and a pore size of up to 28.7 μm; the contact angle is 18°, indicating good hydrophilicity; the breaking strength is 4.8 MPa, and the mechanical properties are excellent compared to the GF membrane.

[0079] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing an electrospun PI@PMIA zinc ion battery separator, characterized in that: The following steps are involved: (1) Preparation of PAA spinning solution: 4,4-diaminodiphenyl ether (ODA) and pyromellitic anhydride (PMDA) were dissolved in N,N-dimethylformamide (DMF) at a molar ratio of 1:1, and a light yellow PAA electrospinning solution with a mass fraction of 18-28% was prepared by mechanical or magnetic stirring; (2) Preparation of PMIA spinning solution: a certain mass fraction of PMIA resin is dissolved in N,N-dimethylacetamide (DMAc), and a uniform and transparent PMIA electrospinning solution with a mass fraction of 25-35% is obtained by mechanical or magnetic stirring; (3) Synchronous multi-needle electrospinning: The two solutions prepared above are transferred to different syringes respectively, the spinning needles are connected to a high voltage power supply, the metal drum is used as a receiving device for PMIA and PAA nanofibers, the spinning voltage of the PAA electrospinning solution is 25-30 kV, the distance between the spinning needle and the receiving device is 17-20 cm, the PAA spinning solution is driven by a micro-injection pump, and the extrusion rate is controlled at 0.7-1.0 mL / h, the PMIA spinning voltage of the electrospinning solution is 30-35 kV, the distance between the spinning needle and the receiving device is 16-18 cm, the PMIA spinning solution is driven by a micro-injection pump, the flow rate is controlled at 0.6-0.8 mL / h, the spinning head diameter is 0.5-0.8 mm, the temperature is 20-30° C., and the humidity is 25-50%; (4) Calcination treatment: Calcination in air, the calcination method includes at least one of hot press heating, muffle furnace heating, and oven heating. During the calcination process, the heating rate of the PAA@PMIA nanofiber membrane is controlled at 2-5°C / min. After the temperature is raised to 280-300°C, the constant temperature is maintained for 1-3 hours, so that the PAA nanofiber completes the subamide process and is converted into PI, thereby obtaining a PI@PMIA nanofiber membrane; The electrospun PI@PMIA zinc ion battery separator is characterized in that the PI nanofibers and the PMIA nanofibers are interwoven and distributed, the fibers are long-range continuous, and the diameters are distributed between 50-500 nm. The porosity of the PI@PMIA zinc ion battery separator is 85-92%, the pore size is 24.6-28.7 μm, the static water contact angle is 10-18°, and the breaking strength is 4.2-4.8 MPa.

Citation Information

Patent Citations

  • Method for preparing lithium battery diaphragm through coaxial electrostatic spinning

    CN110565269A

  • Method for preparing polyacrylonitrile / sulfonated polyetheretherketone lithium-sulfur battery diaphragm material through electrostatic spinning

    CN112768834A